Pengaruh Kompos Tandan Kosong Kelapa Sawit dan Abu Cangkang Kerang Terhadap Serapan Unsur Fosfor dan Produksi Tanaman Jagung Manis di Tanah Ultisols - Pratama, Anggi; Umran, Ismahan; Hayati, Rita (Fakultas Pertanian Universitas Tanjungpura, 2023)
Utilization of Ultisols for sweet maize cultivation has several barriers, especially low of soil acidity, CEC, nutrient availability, organic matter and high of Al, Fe, and Mn consentration. This research was aimed to know the interaction of palm oil empty fruit compost and cockle shell ash on phosphorus uptake and yield of sweet maize in Ultisols. The experiment was carried out in screen house of Agriculture Faculty, Tanjungpura University. The research used factorial design arranged in a completely randomized design (CRD) consisting of two factors treatment (CRD). The first factor is palm oil empty fruit compost consisting control (T0), 670 g/polybag (T1), 1,030 g/polybag (T2) and 1,410 g/polybag (T3). The second factor is cockle shell ash consisting (A0), 3,3 g/polybag (A1), 4,4 g/polybag (A2), and 5,5 g/ polybag (A3). Each tretments was done in 3 replication. The parameters are soil pH, C-Oraganik, P-Available, phosphorus uptake, cob length, and cob weight. The results showed T0A3 can increase soil pH highest with the value 6.08. T3A2 can increase C-Organic with the value 2.31. T2A1 can increase P-Available with the value 26.96. T2 (1,030 g/polybag) significantly affected phosphorus uptake and cob weight.